An acetylcholinesterase-based biosensor of carbofuran using carbon foam electrode modified by graphene and gold particles - Pramadewandaru, Respati Kevin; Triani, Sulis; Tesla, Yudhistira; Sanjaya, Afiten Rahmin (Environmental and Materials, 2025)
Background: This study introduces a novel acetylcholinesterase (AChE)-based biosensor for the sensitive and selective detection of carbofuran, a widely used carbamate pesticide known for its neurotoxicity. Methods: The biosensor employs a carbon foam (CF) electrode modified with graphene oxide and gold nanoparticles (CF/Graphene/Au), leveraging the synergistic properties of these materials to enhance electrochemical performance. Carbofuran detection is achieved through its inhibitory effect on AChE activity, monitored via cyclic voltammetry of thiocholine oxidation. Findings: Under optimal conditions at pH 7.4, the biosensor demonstrated a linear detection range of 25–125 μM, a detection limit of 8.08 μM, and a sensitivity of 0.3874 mA μM⁻¹ cm⁻². It also showed strong reproducibility with a relative standard deviation of 6.77%. When tested on real vegetable samples, the biosensor achieved recovery rates between 88.95% and 111.30%. Conclusion: Compared to existing biosensor technologies, the CF/Graphene/Au-based sensor offers a well-balanced performance in terms of sensitivity, detection range, and practical usability. It presents a viable and portable solution for monitoring pesticide residues in environmental samples. Novelty/Originality of this article:  This work presents a promising, portable solution for environmental monitoring of pesticide residues, integrating advanced nanomaterials and computational validation to improve detection accuracy and reliability.